Molecular Characterization of Functional Domains in the Protein Kinase SOS2 That Is Required for Plant Salt Tolerance - Guo, Yan (American Society of Plant Physiologists, 2001)
The SOS3 (for SALT OVERLY SENSITIVE3) calcium binding protein and SOS2 protein kinase are required for sodium and potassium ion homeostasis and salt tolerance in Arabidopsis. We have shown previously that SOS3 interacts with and activates the SOS2 protein kinase. We report here the identification of a SOS3 binding motif in SOS2 that also serves as the kinase autoinhibitory domain. Yeast two-hybrid assays as well as in vitro binding assays revealed a 21–amino acid motif in the regulatory domain of SOS2 that is necessary and sufficient for interaction with SOS3. Database searches revealed a large family of SOS2-like protein kinases containing such a SOS3 binding motif. Using a yeast two-hybrid system, we show that these SOS2-like kinases interact with members of the SOS3 family of calcium binding proteins. Two-hybrid assays also revealed interaction between the N-terminal kinase domain and the C-terminal regulatory domain within SOS2, suggesting that the regulatory domain may inhibit kinase activity by blocking substrate access to the catalytic site. Removal of the regulatory domain of SOS2, including the SOS3 binding motif, resulted in constitutive activation of the protein kinase, indicating that the SOS3 binding motif can serve as a kinase autoinhibitory domain. Constitutively active SOS2 that is SOS3 independent also was produced by changing Thr(168) to Asp in the activation loop of the SOS2 kinase domain. Combining the Thr(168)-to-Asp mutation with the autoinhibitory domain deletion created a superactive SOS2 kinase. These results provide insights into regulation of the kinase activities of SOS2 and the SOS2 family of protein kinases.